Detection of Organohalide-Respiring Enzyme Biomarkers at a Bioaugmented TCE-Contaminated Field Site - Heavner, Gretchen L. W.; Mansfeldt, Cresten B.; Wilkins, Michael J.; Nicora, Carrie D.; Debs, Garrett E.; Edwards, Elizabeth A.; Richardson, Ruth E. (Frontiers in Microbiology, 2019)
RNA-based biomarkers have been successfully detected at field sites undergoing in situ bioremediation, but the detection of expressed enzymes is a more direct way to prove activity for a particular biocatalytic process of interest since they provide evidence of potential in situ activity rather than simply confirming presence and abundance of genes in a given population by measurement of DNA copies using qPCR. Here we successfully applied shotgun proteomics to field samples from a trichloroethene (TCE)-contaminated industrial site in southern Ontario, Canada that had been bio-augmented with the commercially available KB-1TM microbial culture. The KB-1TM culture contains multiple strains of Dehalococcoides mccartyi (D. mccartyi) as well as an organohalide respiring Geobacter species. The relative abundances of specific enzymatic proteins were subsequently compared to corresponding qPCR-derived levels of DNA and RNA biomarkers in the same samples. Samples were obtained from two wells with high hydraulic connectivity to the KB-1TM-bioaugemented enhanced in-situ bioremediation system, and two control wells that showed evidence of low levels of native organohalide respiring bacteria (OHRB), Dehalococcoides and Geobacter. Enzymes involved in organohalide respiration were detected in the metaproteomes of all four field samples, as were chaperonins of D. mccartyi, chemotaxis proteins, and ATPases. The most highly expressed RDase in the bioaugmentation culture (VcrA) was the most highly detected enzyme overall in the bioaugmented groundwater samples. In one background groundwater well, a Geobacter species appeared to be the most abundant OHRB and had high expression of its PceA enzyme. The DNA and RNA biomarkers detected using qPCR-based assays were a set of orthologs of Dehalococcoides reductive dehalogenases (VcrA, TceA, BvcA, dehalogenase “DET1545”), and the Ni-Fe uptake hydrogenase, HupL. Within a sample, RNA levels for key enzymes correlated with relative protein abundance. These results indicate that laboratory observations of TCE-bioremediation biomarker protein expression are recapitulated in field environmental systems and that both RNA and protein biomarker monitoring hold promise for activity monitoring of in situ populations of OHRB.